Police civilianisation in Canada: a mixed methods investigation - Kiedrowski, John (Policing and society, 2019)
Although the ratio of police officers to population in Canada has been relatively stable since the 1980s there has been a substantial increase in the number of civilians working for police services. To better understand the economic and other consequences of civilianisation, we employed two strategies: an exploratory qualitative examination of the challenges of civilianisation involving a survey and follow-up interviews; and a quantitative analysis of the factors associated with deploying police officer and civilian personnel in 167 municipal police services. When asked about the costs and benefits of civilianisation, police executives reported that the overall number of employees and costs to the police service are not necessarily reduced, as monies saved through civilianisation were spent elsewhere in their organisations: a finding in keeping with a structural contingency perspective. The ordinary least square regression results show that the prevalence of civilian personnel in the police workforce decreases in poorer communities and they are less likely to be employed in larger organisations. There was also a higher prevalence of civilian personnel in police organisations that operated more efficiently. Given these results, a number of suggestions are made for future policy, practice, and research.